Paper’s Entrepreneurship Education and Field Work Practice: ‎Motivational Pathways to Vocational Students’ Interest - Marsha Ovia Permatasari; Ahmad Sehabuddin (Yayasan Darussalam Bengkulu, 2026)
This study examines the effect of entrepreneurship education and field work practice (Praktik Kerja Lapangan/PKL) on vocational students’ entrepreneurial interest, with entrepreneurial motivation positioned as an intervening variable. Using a quantitative explanatory design, data were collected from 181 students of SMK Negeri 10 Semarang who had received entrepreneurship learning and participated in, or were preparing for, field work practice. The research instrument used a five-point Likert scale measuring entrepreneurship education, field work practice, entrepreneurial motivation, and entrepreneurial interest. Data were analyzed through descriptive statistics and partial least squares structural equation modeling (PLS-SEM). The findings show that all constructs were in the high category, with average index scores above 91%. The measurement model met convergent validity and reliability criteria, with AVE values ranging from 0.538 to 0.582 and composite reliability values from 0.880 to 0.906. The structural model indicated strong explanatory power for entrepreneurial motivation (R² = 0.789) and entrepreneurial interest (R² = 0.717). Entrepreneurship education, field work practice, and entrepreneurial motivation significantly influenced entrepreneurial interest, while entrepreneurial motivation also mediated the effects of entrepreneurship education and field work practice. These results imply that vocational schools should not treat entrepreneurship learning and PKL as separate programs, but should integrate them through practice-based, motivationally supportive learning experiences that strengthen students’ confidence, opportunity recognition, and readiness to create new ventures.